Favorable Evaluations of Black and White Women’s Workplace Anger During the Era of #MeToo - McCormick-Huhn, Kaitlin; Shields, Stephanie A. (Frontiers in Psychology, 2021)
Researchers investigating gender and anger have consistently found that White women, but not White men, are evaluated unfavorably when experiencing anger in the workplace. Our project originally aimed to extend findings on White women’s, Black women’s, and White men’s workplace anger by examining whether evaluations are exacerbated or buffered by invalidating or affirming comments from others. In stark contrast to previous research on gender stereotyping and anger evaluations, however, results across four studies (N =1,095) showed that both Black and White women portrayed as experiencing anger in the workplace were evaluated more favorably than White men doing so. After Study 1’s initial failure to conceptually replicate, we investigated whether perceivers’ evaluations of women’s workplace anger could have been affected by the contemporaneous cultural event of #MeToo. Supporting this possibility, we found evaluations were moderated by news engagement and beliefs that workplace opportunities are gendered. Additionally, we found invalidating comments rarely affected evaluations of a protagonist yet affirming comments tended to favorably affect evaluations. Overall, findings suggest the need for psychologists to consider the temporary, or perhaps lasting, effects of cultural events on research outcomes.